Impact of mRNA-based vaccines in the prevention of adverse outcomes of COVID-19 infection in pregnancy: a single-center cohort study - Tudisco, Riccardo; Garufi, Cristina; Rizzo, Francesca; Polimeno, Teresa; Lanzone, Antonio; De Carolis, Sara (Frontiers in Pediatrics, 2023)
Several data suggested that pregnant women have an increased risk of severe COVID-19 compared to those who are not pregnant. Moreover, different studies showed that severe COVID-19 is limited mostly to unvaccinated women. The aim of the present study was to ascertain the different maternal and fetal outcomes in pregnant women with COVID-19 according to the vaccination status. A retrospective cohort study was carried out including all women admitted in the high-risk pregnancy unit of our centre with COVID-19 between December 2021, and February 2022. Among the 163 women included in the study: 60 were vaccinated with mRNA vaccine and 103 were unvaccinated. Pregnancy outcome, obstetrical and neonatal complications were encountered. Vaccinated women showed higher educational level and lower prevalence of cases with BMI >25 compared to unvaccinated women. Moreover, vaccinated women were admitted mostly for obstetrical indications rather than for COVID-related symptoms. In addition, the risk of developing COVID-19 pneumonia was significantly higher in unvaccinated women (p = 0.01) compared with vaccinated ones. Further, pregnancy and neonatal outcome showed some differences in the two cohorts. In unvaccinated women the rate of C-section was higher (p=0.03) and the mean birthweight percentile in infants born resulted impaired by COVID-19 infection (p=0.01) if compared to infants born to vaccinated ones. Based on these results, we suggest that women who received a full course of vaccination on one hand were protected from the severity of the disease, having milder symptoms of SARS-Cov2 infection, on the other hand presented a more favorable pregnancy outcome.